A case study on identify the major problem of high turnover in direct labor at on semiconductor Seremban / Irna Zafirah Rohanuddin - Rohanuddin, Irna Zafirah (Faculty of Business and Management, 2011)
In identifying the major problem of high turnover, the case studies have taken place in on Semiconductor, Seremban. The issue that has been arising in this company is high turn in direct labor. The method that has been used based on total of monthly new hire and resignation, monthly new hire and resignation percentage, overview and interview to a selected staff. Based on the data, the company has a high turnover for a year 2010. Furthermore, the data that been collected shows there are a few reason of high turnover in direct labor towards this company. From this, the recommendation has been inserted as the way to overcome this problem and decreasing the turnover rate with intended of employee retention.